Innovative applications and research advances of bacterial biosensors in medicine - Liu, Mengting; Yang, Wenjie; Zhu, Wenqi; Yu, Daojun (Frontiers in Microbiology, 2025)
The demand for early disease detection, treatment monitoring, and personalized medicine is increasing, making it more imperative than ever to create effective, accurate, portable, intelligent, multifunctional diagnostic equipment. Bacteria possess a remarkable perception of their surroundings and have the capacity to adapt by altering the expression of specific genes. Bacteria interact with target substances and produce detectable signals in response to their presence or concentration. This unique property has been harnessed in the development of bacterial biosensors. Due to groundbreaking advancements in synthetic biology, genetic engineering now enables the creation of bacteria tailored with exceptional detecting traits. In addition to meeting a wide range of application needs, this allows quick and precise detection in intricate settings and offers a strong technological basis for early disease diagnosis and treatment monitoring. This article reviews the applications and recent advancements of bacterial biosensors in the medical field and discusses the challenges and obstacles that remain in their research and application.